2020
DOI: 10.3390/nu12113287
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis subsp. Cremoris C60 restores T Cell Population in Small Intestinal Lamina Propria in Aged Interleukin-18 Deficient Mice

Abstract: Lactic acid bacteria (LAB), a major commensal bacterium in the small intestine, are well known beneficial bacteria which promote establishment of gut-centric immunity, such as anti-inflammation and anti-infection. In this report, we show that a LAB strain Lactococcus lactis subsp. Cremoris C60 possess an ability to activate antigen presenting cells, such as dendritic cells (DCs), and intestinal T cells which possibly support to maintain healthy intestinal immunological environment in aging process. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
1
26
1
Order By: Relevance
“…cremoris SK-11 and HP were both purchased from American Type Culture Collection (ATCC, Manassas, VA, USA). C60 was cultured by following the method described in a previous report [ 17 ]. The SK-11 and HP strains were cultured by following their product data sheets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…cremoris SK-11 and HP were both purchased from American Type Culture Collection (ATCC, Manassas, VA, USA). C60 was cultured by following the method described in a previous report [ 17 ]. The SK-11 and HP strains were cultured by following their product data sheets.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that Lactococcus lactis subsp. cremoris C60, a probiotic LAB strain, promoted the generation and activation of CD4+ T cells in the small intestine [ 17 ]. As an underlying mechanism, we revealed that a heat-killed C60 (HK-C60) diet promoted not only cytokine production but also antigen-presenting activity for CD4+ T cells in intestinal DCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow (BM) cells were obtained from the tibia and femur as previously reported ( 17 ). Briefly, the cells were flushed out from the tibia and femur using a 10 mL syringe with a 27 G needle containing cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study of aged IL-18-deficient mice found that Lactococcus lactis subsp. cremoris C60 restored T cell populations in small intestinal lamina propria, which led to a rebound in IFN-γ production in the CD4 + T cell population [ 102 ]. Similarly, the probiotic strains Lactobacillus plantarum and Lactobacillus.…”
Section: Probiotics In Crcmentioning
confidence: 99%